2023
DOI: 10.3389/fimmu.2023.1094823
|View full text |Cite
|
Sign up to set email alerts
|

The role of Th-17 cells and IL-17 in the metastatic spread of breast cancer: As a means of prognosis and therapeutic target

Abstract: Metastatic breast cancer is one of the most common and well-known causes of death for women worldwide. The inflammatory tumor cell and other cancer hallmarks dictate the metastatic form and dissemination of breast cancer. Taking these into account, from various components of the tumor microenvironment, a pro-inflammatory infiltrative cell known as Th-17 plays an immense role in breast cancer proliferation, invasiveness, and metastasis. It has been demonstrated that IL-17, a pleiotropic pro-inflammatory cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 156 publications
0
4
0
Order By: Relevance
“…Moreover, it has been reported that the tumor-infiltrating γδT17 subset mediating pro-angiogenic IL-17 thereby inducing the expression of VEGF-A, CXCL8, GM-CSF, and TNFα release, can actively participate in the angiogenic process and the recruitment of MDSCs ( Wu et al, 2014 ). IL-17 also indirectly promotes angiogenesis by activating the expression of CCL17 and CCL22 and facilitates Treg cell migration to tumor ( Shibabaw et al, 2023 ).…”
Section: Signaling From Immune Cells To Tecsmentioning
confidence: 99%
“…Moreover, it has been reported that the tumor-infiltrating γδT17 subset mediating pro-angiogenic IL-17 thereby inducing the expression of VEGF-A, CXCL8, GM-CSF, and TNFα release, can actively participate in the angiogenic process and the recruitment of MDSCs ( Wu et al, 2014 ). IL-17 also indirectly promotes angiogenesis by activating the expression of CCL17 and CCL22 and facilitates Treg cell migration to tumor ( Shibabaw et al, 2023 ).…”
Section: Signaling From Immune Cells To Tecsmentioning
confidence: 99%
“…In most of these studies, IL17-producing T-cells have been associated with disease progression, worse prognosis, triple-negative molecular subtypes, shorter disease-free survival (DFS), and genes related to the tumors' proliferation and survival [54][55][56]. The pro-tumor properties of Th17 cells in BC (Figure 2) are attributed to multiple mechanisms, including the regulation of angiogenesis, induction of pro-invasive factors (i.e., IL-17, IL-22, and IL-23), metalloproteinases (MMPs) that promote proliferation, survival, and the invasion of malignant cells, interfering with CD8 + T-cell migration through the activation of STAT3 signaling and subsequent reduction of CXCR3 expression [57][58][59][60]. The role of IL-17 in angiogenesis is enhanced through the induction of angiogenic factors such as MMP-2, MMP-9, vascular endothelial growth factor (VEGF), and CXCL8 [61].…”
Section: Th17 In Breast Carcinomamentioning
confidence: 99%
“…Additionally, in metastatic breast cancer, up-regulation of IL-17 expression promotes MAPK activation, which leads to NF-kB pathway-mediated overexpression of MMP signaling. This, in turn, promotes tumour cell proliferation and metastasis [ 33 ].…”
Section: The Roles Of Tumour-promoting Role Of the Inflammatory Micro...mentioning
confidence: 99%